2020
DOI: 10.36519/idcm.2020.0020
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of COVID-19 Patients Hospitalized in a University Hospital, Turkey

Abstract: Background: We aimed to assess the risk factors for severe COVID-19 and investigate the differences between intensive care unit (ICU) and non-ICU patients. Method: The clinical, radiological, and laboratory characteristics of confirmed COVID-19 patients between March 15, 2020, and May 30, 2020, were evaluated retrospectively. Results: A total of 157 patients were included in the study. The median age of the patients was 47, and 55% were male. Seventeen of them were treated in ICU. All of the patients who were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…In association, there is an increase in D-dimer levels. Studies have indicated that increases in D-dimer levels are an important marker to detect critical disease early ( 26 , 27 ). In this regard, our study supports the literature.…”
Section: Discussionmentioning
confidence: 99%
“…In association, there is an increase in D-dimer levels. Studies have indicated that increases in D-dimer levels are an important marker to detect critical disease early ( 26 , 27 ). In this regard, our study supports the literature.…”
Section: Discussionmentioning
confidence: 99%
“…14% of 157 individuals were diagnosed with diabetes mellitus (DM). 38 In USA a study conducted where it showed the prevalent of diabetes was 58% with the average age of the patients was 64, 63% were males, 39 while another survey showed 10.9%. 40 Another study conducted for a short period of time where the prevalence is found to be above 50%.…”
Section: Literature Review 131 Review Of Related Literaturementioning
confidence: 99%